Nonneoplastic Tongue Swellings of Lymphatic and Lymphocytic Origin: Three Case Reports - Manar A. Abdul Aziz; Nermin M. Yussif (Hindawi Limited, 2016)
Tongue is formed of a mass of muscles and salivary gland embedded in anterior highly vascular and posterior lymphoid stroma and covered by specialized surface epithelium. Growths from all of these heterogonous components may occur resulting in a wide variation in clinical features and behavior, ranging from self-limiting to aggressive lesions. Therefore, surgical excision is the treatment of choice. The aim of the current study is to report three different lesions that came to the Oral Surgery Department in the Faculty of Oral and Dental Medicine, Cairo University. Following clinical and histopathological examination, the diagnosis of reactive lymphoproliferative lesion, cystic lymphoepithelial lesion, and developmental lymphatic vessel malformation was reached.